O aguapé e o biocarvão: uma revisão bibliométrica baseada na base Scopus - de Lima Girão, Lucas Henrique; Freitas de Andrade, Carla; M. de Oliveira, Mona Lisa; M. Carneiro, Francisco Olímpio; Silveira Serra, Daniel; de Andrade Araújo, Lívia Maria (Latin American Journal of Energy Research, 2025)
Water hyacinth (Eichhornia crassipes) is an aquatic plant whose characteristic is its high growth and proliferation in its environment. Because of these aspects, this type of raw material can be used as biomass applied to renewable technologies. In recent years, studies on the production of biochar through the application and optimization of the pyrolysis process have been widely discussed as a sustainable solution for biomass management through the production of important co-products: biochar (solid part), bio-oil (liquid part) and non-condensable gases (NCG). This study presents a literature review on the application of water hyacinths in the biochar production process through a bibliometric analysis carried out using the Biblioshiny tool and a search in the Scopus database. The results point to an increase in scientific production, linked to academic interest in the subject and with an emphasis on research that discusses the pyrolysis process, the application of water hyacinth as biomass and the use of biochar in the environment.